Impact of Bubbles Map strategy on developing science operations’ skills for 5th grade literary students in the subject of rhetoric and application - Fleeh Hassan, Ahmed; Abdul Qadir Aziz Al-Khalidi, Sondos; Majeed Hammadi, Haider (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to know the effect of the strategy of map bubbles on developing the skills of science operations among 5th grade literary students in the subject of rhetoric and application, and the design of the experimental and control groups with the pre- and post-tests was used. The research sample consisted of (50) students divided into two groups: an experimental group of which the number of its members reached (25) students and studied using the strategy of map bubbles, and a control group of which the number of its members reached (25) students and studied in the traditional (standard) method. The researchers prepared a multiple-choice achievement test with several (30) paragraphs, and its validity and consistency were extracted. Then the test was applied to the sample before and after, and the actual results reached by the research were There is a statistically significant difference between the mean scores of the experimental group who study the rhetoric and application subject using the bubble map in the pre- and post-tests in developing the skills of science operations as a whole, and there is no statistically significant difference between The average scores of the control group students who study rhetoric and application in the traditional (standard) method in the pre- and post-tests in developing the skills of the science processes as a whole, and finally, there is a statistically significant difference between the average scores of the students of the experimental group who are studying rhetoric and application using the map of bubbles and the average scores of the students of the traditional (standard) control group in the post-test in developing the skills of science operations as a whole.